The end of fundraising : raise more money by selling your impact - Saul, Jason, 1969- (Jossey-Bass, 2011)
"Strategy guide for nonprofits seeking to fundraise and "sell" their impact in today's social change marketplace For too long, nonprofits have had to live off of the "waste products" of the economy: leftover money (donations) and leftover time (volunteering). But the advent of the social capital market? where social change now has real economic value? gives nonprofits the opportunity to sell their impact to a new set of stakeholders: corporations, investors, government agencies, service providers and consumers. Based on years of experience advising the world's leading foundations, corporations, and government agencies, Saul shares key secrets on how funders think and what it takes to convince them. Includes tools for nonprofits to learn how to effectively frame, market, and sell their impact Contains step-by-step guidance on how to create leverage with different types of funders Saul is the author of Benchmarking for Nonprofits, selected as the Independent Publishers Association Best Business Book of the Year This groundbreaking book explodes the old paradigm of fundraising as charity and teaches nonprofits how to create leverage through delivering results to those who value them the most"--